2004
DOI: 10.1111/j.1464-5491.2004.01114.x
|View full text |Cite
|
Sign up to set email alerts
|

Hospital outcome of acute myocardial infarction in patients with and without diabetes mellitus

Abstract: In diabetic patients with acute myocardial infarction, early hospital mortality is increased and signs of cardiac autonomic dysfunction and microangiopathy are detected more frequently than in non-diabetic patients. The need for advanced treatment strategies early in the course of diabetic patients with myocardial infarction is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 29 publications
1
36
1
5
Order By: Relevance
“…The prognosis of diabetic patients with acute coronary syndrome is worsened by presence of other risk factors associated in metabolic syndrome, such as hypertension, obesity and dyslipidaemia (Zuanetti et al 1993;Behar et al 1997;Vaccaro et al 2004;Otter et al 2004;Howard et al 2006). The benefits of cardiac rehabilitation programs in patients with CAD both in programs with only aerobic exercise training (Oldridge et al 1988;O'Connor et al 1989;Yoshida et al 2001;Taylor et al 2004Taylor et al , 2006 and in those with resistance or combined aerobicresistance exercise (Stewart et al 1998;Adams et al 1999;Jancik et al 2003;Izawa et al 2004;Vincent and Vincent 2006) have been repeatedly reported.…”
Section: The Exercise Programmentioning
confidence: 99%
“…The prognosis of diabetic patients with acute coronary syndrome is worsened by presence of other risk factors associated in metabolic syndrome, such as hypertension, obesity and dyslipidaemia (Zuanetti et al 1993;Behar et al 1997;Vaccaro et al 2004;Otter et al 2004;Howard et al 2006). The benefits of cardiac rehabilitation programs in patients with CAD both in programs with only aerobic exercise training (Oldridge et al 1988;O'Connor et al 1989;Yoshida et al 2001;Taylor et al 2004Taylor et al , 2006 and in those with resistance or combined aerobicresistance exercise (Stewart et al 1998;Adams et al 1999;Jancik et al 2003;Izawa et al 2004;Vincent and Vincent 2006) have been repeatedly reported.…”
Section: The Exercise Programmentioning
confidence: 99%
“…In our own experience, the MS prevalence is similar in subjects with impaired glucose tolerance and newly diagnosed type 2 diabetes (T2DM; 44% and 56%, respectively) [8]. The strong association between glucose and CV risk is also supported by the prognostic value of a random blood glucose measurement in the occasion of acute coronary syndrome [9].…”
Section: Introductionmentioning
confidence: 57%
“…Der Nutzen der Infusion mit Glucose und Humaninsulin im intensivmedizinischen Umfeld könnte auch partiell durch eine Optimierung der Herznervenfunktion in der Akutphase bedingt sein [2,23]. Die häufi-ge autonome Dysfunktion bei Diabetikern mit akutem Myokardinfarkt, die in einer erhöhten Ruhefrequenz und selteneren Angabe pektanginöser Beschwerden deutlich wird, unterstreicht die Notwendigkeit einer Optimierung der autonomen Funktion während der intensivmedizinischen Betreuung [22].…”
Section: Diskussionunclassified